Ultra-low jitter clock distribution for the trigger electronics of the New Small Wheel for the ATLAS experiment. (1st May 2022) - Alexopoulos, T.; Geralis, T.; Gkountoumis, P.; Levinson, L.; Mesolongitis, I.; Zormpa, O.
Abstract: The Large Hadron Collider (LHC) at CERN plans to have a series of upgrades to increase its instantaneous luminosity to 7.5 × 10 34 cm −2 s −1 . The increased luminosity drastically impacts the ATLAS trigger and readout data rates. The inner-most station of the ATLAS muon spectrometer, the so-called Small Wheels is being replaced with a New Small Wheel (NSW) system, consisting of Micromegas and small-strip Thin Gap Chambers (sTGC) detectors. The on-detector radiation levels required radiation tolerant electronics. The lower radiation levels on the rim of the NSW allowed utilizing commercial electronic chips, such as Field Programmable Gate Arrays (FPGAs), in the trigger chain of the sTGC detectors. Those FPGAs require an ultra-low jitter clock for the proper operation of their Gigabit transceivers (4.8 Gb/s serial links). The initial design was based on a clock provided by a radiation tolerant ASIC designed at CERN, but due to its intrinsic jitter and consequent marginal error rate on the transmission lines, a different approach had to be chosen. An additional clock source based on commercial jitter cleaners, fanout chips and optical transmitters driving dedicated fibers was built. The new scheme provides 64 low-jitter clocks (32 main and 32 redundant) from the radiation-protected area (USA15) to the trigger electronics over 60 m of OM3 fiber.